زواج القاصرات المعاصر وبيان الاختلاف عليه في ضوء الشريعة الإسلامية - Shahin Gahin Hamed Gahin Metawee; Mohammed Muneer'deen Olodo Al-Shafi'i (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
Contemporary child marriage has become a noticeable phenomenon in recent times, spreading rapidly and extensively. This research aims to clarify the concept of minors and elucidate the reasons and motivations behind the prevalent phenomenon of child marriage, both in the past and in contemporary society. The study reveals that there are social, economic, health, and psychological factors contributing to this issue. The research adopted a descriptive and inductive approach to investigate the reasons for marrying minors, based on an analysis of books and studies that discussed the motives for such marriages and the legal rulings on marrying minors. Additionally, the negative consequences of child marriages were examined. The research yielded findings, including the definition of a minor as someone who has not reached the legal age for marriage and is incapable of assuming marital responsibilities. The economic circumstances of the guardian sometimes force them to marry off their daughters to avoid the financial burden. Some parents resort to informal marriages, which the law prohibits, thus denying minors their rights. The study also highlighted the physical and mental health risks associated with child marriages, such as weakened immunity, diabetes, high blood pressure, and other health issues. Research has also documented cases of minors dying within a year of marriage. In conclusion, this research contributes to clarifying the concept of minors, uncovering the reasons for child marriages, and explaining the legal rulings regarding such unions.